Prolonged use of an Arndt Endobronchial Blocker with Radiocontrast Dye in a Neonate - Michael Kaczmarski; Neethu Chandran; Ranjith Vellody; Bhupender Yadav; Richard Kaplan (Global Journal of Anesthesiology - Peertechz Publications, 2017)
Lung isolation management has long been a complicated issue in the neonatal patient due to the patient's size which limits the ability to use many of the devices used in the adult patient. The Arndt bronchial blocker is now available in sizes that allow lung isolation to be feasible in the pediatric patient. Traditionally, use of the Arndt bronchial blocker has been limited to short term use in the operating room. This case report discusses the use of the Arndt bronchial blocker for an extended period of time in the Cardiac Intensive  Care Unit (CICU) to successfully treat multiple unilateral pneumatoceles in a neonate and in the process avoid the use of Extracorporeal Membrane Oxygenation (ECMO) and its associated risks. It also describes the use of radiocontrast dye in the bronchial blocker cuff in order to facilitate identification of cuff position by subsequent chest xrays.